2010
DOI: 10.2320/matertrans.mj201018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Dwelling Time on Low-Cycle Fatigue Characteristic of Isotropic Conductive Adhesive Joint

Abstract: The effects of temperature and dwell time on the low-cycle fatigue life of Ag-epoxy based conductive adhesive have been investigated by using a micro-joint specimen. The low cycle fatigue life of the conductive adhesive increases when test temperature is elevated beyond the glass transition point. On the other hand, the dwell time at 398 K reduces the fatigue life, which, however, is increased by the dwell time at 348 K. The cross-sectional image suggests the embrittlement of epoxy resin during the dwell time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…This is different from the results reported by Andersson and Lau, who found that the maximum load drop began at stable state [16]. Many workers attributed the load drop to the reduction of load-bearing area or the initiation and subsequent propagation of fatigue crack [13,17]. Obviously, this could not explain the first stage in this test result.…”
Section: Methodscontrasting
confidence: 83%
“…This is different from the results reported by Andersson and Lau, who found that the maximum load drop began at stable state [16]. Many workers attributed the load drop to the reduction of load-bearing area or the initiation and subsequent propagation of fatigue crack [13,17]. Obviously, this could not explain the first stage in this test result.…”
Section: Methodscontrasting
confidence: 83%
“…3 was used in the experiment. 3,12,13 This machine employs a piezo-stage actuator with a displacement enlargement mechanism. The maximum stroke is ±250 lm, and the maximum load is ±40 N. The displacement was measured using an electrical capacitance displacement sensor (displacement resolution of 0.01 lm) positioned at the end of the specimen-fixing jig, and the actuator was controlled by the measured values of the displacement sensor.…”
Section: Low-cycle Fatigue Testing Methodsmentioning
confidence: 99%
“…11) This machine employs a piezostage actuator with a displacement enlargement mechanism; the maximum stroke is «250 µm and the maximum load is «40 N. The displacement was measured using an electrical capacitance displacement sensor (displacement resolution: 0.01 µm) positioned at the end of the specimen-fixing jig, and the actuator was controlled by the values measured by the displacement sensor. The specimen-fixing jig was heated by a ceramic heater placed at the bottom of the jig; the temperature was monitored to remain within «2 K by a thermocouple attached to the specimen.…”
Section: Mechanical Testing Machinementioning
confidence: 99%